(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
With urban expansion and densification escalating, Small Urban Parks (SUPs) have emerged as crucial components in urban landscapes, offering diverse ecosystem benefits. This paper aims to achieve two primary objectives: (i) conduct an extensive analysis of Malaysia’s national climate and planning policies, evaluating their incorporation of preservation open spaces and interconnected climate change considerations, and (ii) explore sustainable strategies for SUP management, underlining their contribution to cultivating green, low-carbon urban environments. The study employs a content analysis approach to examine Malaysia’s environmental policy documents, gauging their alignment with the objective of utilizing open spaces for climate change mitigation. The findings emphasize the importance of embedding SUPs in urban planning as a strategic approach to carbon sequestration and highlight the pivotal role of local authorities in realizing a carbon-neutral urban vision by 2050. Supported by robust policy frameworks and grassroots endeavors, urban green spaces, regardless of their size, can make significant strides towards a sustainable urban future.